Youth Within Transition: Recent Developments in Education and Employment in Yogyakarta - Alexander Michael Tjahjadi; derajad sulistyo Widhyharto (Universitas Gadjah Mada, 2017)
Yogyakarta as a parameter for the development of national education offers potential young and educated human resources. It is hoped that this potential will trigger youth’s productivity to contribute in the demographic bonus and national development. From the perspective of economic growth, Yogyakarta tends to have an increasing trend when compared to that of national economy which tends to decline. However, the increasing trend can become a problem when the educated youth are unproductive and fails to transition from education field to working field. The data of Yogyakarta’s GDRP from 2003 to 2013 shows a dependency on the trading, tourism and services sectors. Optimism towards those three sectors do show a percentage increase, but it is not in sync with the education potential and employment for the youth. There is a transition from young labour who are self- or family-employed into low-rank employees and paid labor. There are at least two effects of this phenomenon. First, the data shows that the number of unemployed youth become stagnant with high school as the highest completed education. This indicates a hindrance for transition among youth from secondary education to higher education. Second, this obstacle prevents youth from moving into a higher income bracket and traps them in below-average wages. In reality, economic growth is still reliant on the services and consumption sectors, thus a transitory approach is needed that can involve the youth not as an object but as a main feature of Special Region of Yogyakarta is needed.